2012
DOI: 10.1002/aqc.2252
|View full text |Cite
|
Sign up to set email alerts
|

Using a process‐based catchment‐scale model for enhancing field‐based stream assessments and predicting stream fish assemblages

Abstract: 1. Catchment-modelling techniques, although not yet widely used in biological contexts, may be a valuable tool in the management and conservation of stream fishes. This study was undertaken to evaluate the potential of a catchment-scale hydrologic model, the Soil and Water Assessment Tool (SWAT), to explain characteristics of stream fish assemblages and to enhance current field-based stream assessments.2. Stream fish assemblages, instream habitat, geomorphology, and water quality were surveyed in 16 study catc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…The Soil and Water Assessment Tool (SWAT) is a physically based watershed model that incorporates spatial datasets of elevation, land use, soil, weather, and field management into a simulation of surface and subsurface hydrology and fluxes of chemicals and sediments (Arnold, Srinivasan, Muttiah, & Williams, 1998; Neitsch, Arnold, Kiniry, Williams, & King, 2002). The use of the SWAT model to link nutrients with biological integrity is a relatively new approach, but initial research has indicated that it is a potentially useful tool (Einheuser et al., 2012; Einheuser, Nejadhashemi, Wang, Sowa, & Woznicki, 2013; Kautza, Mazeika, & Sullivan, 2012; Woznicki et al., 2015, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Soil and Water Assessment Tool (SWAT) is a physically based watershed model that incorporates spatial datasets of elevation, land use, soil, weather, and field management into a simulation of surface and subsurface hydrology and fluxes of chemicals and sediments (Arnold, Srinivasan, Muttiah, & Williams, 1998; Neitsch, Arnold, Kiniry, Williams, & King, 2002). The use of the SWAT model to link nutrients with biological integrity is a relatively new approach, but initial research has indicated that it is a potentially useful tool (Einheuser et al., 2012; Einheuser, Nejadhashemi, Wang, Sowa, & Woznicki, 2013; Kautza, Mazeika, & Sullivan, 2012; Woznicki et al., 2015, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For stream fishes, reproductive success is directly tied to reproductive traits, particularly spawning modes (Wootton, ). Among the reproductive guilds described by Balon (), lithophilic (requiring clean gravel spawning substrate) fishes are often disproportionately affected by land‐use change associated with human development (Berkman and Rabeni, ; Kautza and Sullivan, ). As a consequence, lithophilic stream fishes usually comprise the majority of imperiled freshwater fishes (Jelks et al ., ).…”
Section: Introductionmentioning
confidence: 99%